Komplikationen und Erfolgsraten des Vena-subclavia-Katheters in Abhängigkeit der Erfahrung - Schulz, Johannes (Anaesthesist, 2020)
BACKGROUND: The infraclavicular puncture of the subclavian vein is a standard procedure for anesthetists. Meanwhile the literature and recommendations are clear and the use of real-time ultrasound guidance is the standard procedure; however, anesthetists will always get into special circumstances were they have to use the landmark technique, so this competence must be preserved. Feared complications of infraclavicular subclavian vein puncture are pneumothorax and arterial puncture. Up to now there is no clear learning curve for the infraclavicular subclavian vein puncture in the landmark technique performed by anesthetists. OBJECTIVE: The aim of this study was to examine the influence of the puncture experience on the success rate and mechanical complications, such as pneumothorax and arterial puncture in patients who received an infraclavicular subclavian vein puncture with the landmark technique. Three levels of experience were defined for comparison: inexperienced 0–20 punctures, moderately experienced 21–50 and experienced over 50 punctures. MATERIAL AND METHODS: Post hoc analysis of a previously published noninferiority study to examine the influence of ventilation on the pneumothorax rate in the subclavian vein puncture using the landmark technique. This analysis included 1021 anesthetized patients who were included in the original study between August 2014 and October 2017. Demographic data as well as the number of puncture attempts, puncture success, the overall rate of mechanical complications, pneumothorax rate and arterial puncture rates were calculated. RESULTS: The overall rate of mechanical complications (pneumothorax + arterial puncture) was significantly higher in the inexperienced group (0–21) compared to the experienced group (>50, 15% vs. 8.5%, respectively, p = 0.023). This resulted in an odds ratio of 0.52 (confidence interval, CI: 0.32–0.85, p = 0.027). Likewise, the rate of puncture attempts in the group of inexperienced (0–20) with 1.85 ± 1.12 was significantly higher than in the group of experienced (>50, 1.58 ± 0.99, p = 0.004) and resulted in an odds ratio of 0.59 (CI: 0.31–0.96, p = 0.028). Although the puncture attempts of the moderately experienced (21–50) compared to the inexperienced (0–20) was not significant lower, we found an odds ratio of 0.69 (CI: 0.48–0.99, p = 0.042). The rate of successful puncture was 95.1% in the experienced group versus 89.3% in the inexperienced group (p = 0.001), which resulted in an odds ratio of 2.35 (CI: 1.28–4.31, p = 0.018). When viewed individually, no significant differences were found for pneumothorax and arterial puncture. CONCLUSION: In this post hoc analysis of the puncture of the subclavian vein using the landmark technique, we found a significant reduction of puncture attempts and overall mechanical complications. At least 50 punctures seem to be necessary to achieve the end of the learning curve; however, the landmark technique should only be used under special circumstances, when real-time ultrasound is not available. Anesthetists who want to complete their repertoire and learn the landmark technique should always perform a static ultrasound examination before starting the puncture in order to reduce complications due to anatomical variations or thrombosis.